Preparation and Characterization of Thermoresponsive Poly(N-isopropylacrylamide-co-acrylic acid)-Grafted Hollow Fe(3)O(4)/SiO(2) Microspheres with Surface Holes for BSA Release - Zhao, Jing (Materials (Basel), 2017)
Thermoresponsive P(NIPAM-AA)/Fe(3)O(4)/SiO(2) microspheres with surface holes serving as carriers were prepared using p-Fe(3)O(4)/SiO(2) microspheres with a thermoresponsive copolymer. The p-Fe(3)O(4)/SiO(2) microspheres was obtained using a modified Pickering method and chemical etching. The surface pore size of p-Fe(3)O(4)/SiO(2) microspheres was in the range of 18.3 nm~37.2 nm and the cavity size was approximately 60 nm, which are suitable for loading and transporting biological macromolecules. P(NIPAM-AA) was synthesized inside and outside of the p-Fe(3)O(4)/SiO(2) microspheres via atom transfer radical polymerization of NIPAM, MBA and AA. The volume phase transition temperature (VPTT) of the specifically designed P(NIPAM-AA)/Fe(3)O(4)/SiO(2) microspheres was 42.5 °C. The saturation magnetization of P(NIPAM-AA)/Fe(3)O(4)/SiO(2) microspheres was 72.7 emu/g. The P(NIPAM-AA)/Fe(3)O(4)/SiO(2) microspheres were used as carriers to study the loading and release behavior of BSA. This microsphere system shows potential for the loading of proteins as a drug delivery platform.